Evaluating participatory group mentoring in international development projects in the Middle East. Issue 4 (18th May 2020) - Refki, Dina; Mishkin, Kathryn; Johnson, September
ABSTRACT: Agents of sustainable international development seek to impact community transformation through developing the capacity of stakeholders. This article analyses six semi-structured interviews with mentors from two international development projects in the Middle East. Programmes sought to advance international development and human rights in a region challenged by political and social barriers. Analysis of the mentorship cases revealed that mentors used approaches that applied transformational leadership concepts in the form of idealised influence, inspirational motivation, individualised consideration and intellectual stimulation. Approaches used by mentors were examples of the Taxonomy of Significant Learning used to facilitate deep and independent learning.